2005
DOI: 10.1002/cne.20851
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation in the forebrain and midbrain of the sea lamprey

Abstract: Cell proliferation in the forebrain and midbrain of the sea lamprey (Petromyzon marinus L.) was investigated by proliferation cell nuclear antigen (PCNA) immunocytochemistry, with BrdU labeling as a complementary technique. Correspondence between proliferation regions and areas of early neuronal differentiation was also assessed using antibodies against HNK-1 early differentiation marker. The brain of late embryos shows a homogeneously thick ventricular zone (VZ) containing PCNA-immunoreactive (PCNA-ir) nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 77 publications
5
38
0
Order By: Relevance
“…Cell proliferation was also monitored by using a mouse monoclonal anti-rat PCNA (1:100; clone PC10; Reference MO879, DAKO). This antibody has been shown to react with proliferating cell nuclear antigen (PCNA) in a wide range of species including fish and causes nuclear staining similar to BrdU, as previous studies have shown (Wullimann and Puelles, 1999;Bang et al, 2001;Villar-Cheda et al, 2006). PCNA antibody specificity was tested by the supplier.…”
Section: Antibodiesmentioning
confidence: 99%
“…Cell proliferation was also monitored by using a mouse monoclonal anti-rat PCNA (1:100; clone PC10; Reference MO879, DAKO). This antibody has been shown to react with proliferating cell nuclear antigen (PCNA) in a wide range of species including fish and causes nuclear staining similar to BrdU, as previous studies have shown (Wullimann and Puelles, 1999;Bang et al, 2001;Villar-Cheda et al, 2006). PCNA antibody specificity was tested by the supplier.…”
Section: Antibodiesmentioning
confidence: 99%
“…In a recent important analysis of neuronal proliferation and differentiation in the brain of embryonic, larval and adult lamprey (Petromyzon marinus), proliferation has been correlated to lamprey brain morphogenesis (Villar-Cheda et al 2006). These authors have shown that differences in the thickness and appearance of the ventricular zone (the portion of the neural tube closest to the ventricle), as well as the presence of proliferation discontinuities, correspond to distinct neuroanatomical regions.…”
Section: Atypical Proliferation and Neurogenesis Patternsmentioning
confidence: 99%
“…The immunostaining was developed with 0.6 mg/ml 3-3Ј-diaminobenzidine (DAB; Sigma) and 0.003% H 2 O 2 . PCNA antibody specificity was tested by the supplier, and it was shown that in the lamprey brain it only stains cells in the proliferating ventricular zone (Villar-Cheda et al, 2005, 2006b). Furthermore, no immunostaining was observed in sections processed without the primary antibody.…”
Section: Pcna Immunocytochemistrymentioning
confidence: 99%
“…Lamprey larvae (n ϭ 3) were placed in 1% BrdU (Sigma) in freshwater for 6 days following previous studies in the larval brain (Villar-Cheda et al, 2006b), in order to label a substantial proportion of cells in these slow-proliferating vertebrates. They were then anesthetized with benzocaine and fixed by immersion in Clarke's fixative (75% ethanol, 25% acetic acid), embedded in paraffin, and cut (10 m thickness) on a rotary microtome.…”
Section: Brdu Labelingmentioning
confidence: 99%
See 1 more Smart Citation